Glucosamine Protects Neonatal Cardiomyocytes from Ischemia-Reperfusion Injury via increased protein O-GlcNAc and increased mitochondrial Bcl-2 - Champattanachai, Voraratt (2008)
We have previously reported that glucosamine protected neonatal rat ventricular myocytes (NRVMs) against ischemia/reperfusion (I/R) injury, and this was associated to an increase in protein O linked-N-acetylglucosamine (O-GlcNAc) levels. However, the protective effect of glucosamine could be mediated via pathways other that O-GlcNAc formation; thus, the initial goal of this study was to determine whether increasing O-GlcNAc transferase (OGT) expression, which catalyzes the formation of O-GlcNAc, had similar protective effect as glucosamine. To better understand the potential mechanism underlying O-GlcNAc-mediated cytoprotection we examined whether increased O-GlcNAc levels altered the expression and translocation of members of the Bcl-2 protein family. Both glucosamine (5mM) and OGT overexpression increased basal and I/R induced O-GlcNAc levels, significantly decreased cellular injury, and attenuated loss of cytochrome C. Both interventions also attenuated the loss of mitochondrial membrane potential induced by H(2)O(2) and were also associated with an increase in mitochondrial Bcl-2 levels, but had no effect on Bad on Bax levels. Compared to glucosamine and OGT overexpression, NButGT (100 µM), an inhibitor of O-GlcNAcase, was less protective against I/R and H(2)O(2) and did not affect Bcl-2 expression, despite a 5 to 10 fold greater increase in overall O-GlcNAc levels. Decreased OGT expression resulted in lower basal O-GlcNAc levels, prevented the I/R induced increase in O-GlcNAc and mitochondrial Bcl-2 and increased cellular injury. These results demonstrate that the protective effects of glucosamine are mediated via increased formation of O-GlcNAc and suggest that this is due in part to enhanced mitochondrial Bcl-2 translocation.